Treatment-Limiting Decisions in Patients with Spontaneous Intracerebral Hemorrhage - Felix Lehmann; Matthias Schneider; Joshua D. Bernstock; Christian Bode; Valeri Borger; Stefan Felix Ehrentraut; Florian Gessler; Anna-Laura Potthoff; Christian Putensen; Lorena M. Schenk; Julian Zimmermann; Hartmut Vatter; et al. (Medicina, 2022)
Background and Objectives: Treatment-limiting decisions (TLDs) are employed to actively withhold treatment/invasive interventions from patients in whom clinicians feel they would derive little to no benefit and/or suffer detrimental effects. Data regarding the employment of TLDs in patients with spontaneous intracerebral hemorrhage (ICH) remain sparse. Accordingly, this study sought to investigate both the prevalence of TLDs and factors driving TLDs in patients suffering from spontaneous ICH. Materials and Methods: This was a retrospective study of 249 consecutive patients with ICH treated from 2018–2019 at the Neurovascular Center of the University Hospital Bonn. Reasons deemed critical in the decision-making process with regard to TLD were ultimately extracted/examined via chart review of qualifying patients. Results: A total of 249 patients with ICH were included within the final analyses. During the time period examined, 49 patients (20%) had advanced directives in place, whereas in 53 patients (21%) consultation with relatives or acquaintances was employed before further treatment decisions. Overall, TLD ultimately manifested in 104 patients (42%). TLD was reached within 6 h after admission in 52 patients (50%). Congruent with severity of injury and expected outcomes, TLDs were more likely in patients with signs of cerebral herniation and an ICH score > 3 (p < 0.001). Conclusions: The present study examines details associated with TLDs in patients with spontaneous ICH. These data provide insight into key decisional processes and reinforce the need for further structured investigations in an effort to help guide patients and their families.